Teaching Agility in Inclusive Education: A Phenomenological Study of Assistant Teachers in Indonesia - Mulyani, Esti (LifeSciFi, 2025)
Inclusive education aims to guarantee equal educational rights for children with special needs in regular schools. In its implementation, assistant teachers are required to have teaching agility, namely the ability to adapt quickly and flexibly to the diverse learning needs of students. Empirical studies that specifically explore how teaching agility is developed and experienced by assistant teachers, particularly from their own lived experiences, remain limited. This study aims to explore the experiences of assistant teachers in developing teaching agility in the context of inclusive education. The study used a qualitative approach with a phenomenological method. The research subjects consisted of two assistant teachers. Data were collected through observation, in-depth interviews, and documentation, then analyzed through reduction, presentation, and drawing conclusions. The results of the study indicate that teaching agility develops through understanding student character, teaching experience, school environmental support, curriculum flexibility, and teacher personal motivation, despite still facing limitations in training and facilities. This study contributes by providing in-depth insights into the practical formation of teaching agility, which can inform teacher development programs and inclusive education policy implementation.